The EPS-I exopolysaccharide transforms Ralstonia wilt pathogen biofilms into viscoelastic fluids for rapid dissemination in planta - Matthew L. Cope-Arguello; Jiayu Li; Zachary Konkel; Nathalie Aoun; Tabitha Cowell; Nicholas Wagner; A. Li Han Chan; Lan Thanh Chu; Samantha Wang; Mariama D. Carter; Caitilyn Allen; Lindsay J. Caverly; et al. (Proceedings of the National Academy of Sciences, 2026)
Ralstonia solanacearum species complex (RSSC) pathogens cause destructive plant wilt diseases of a wide variety of crops, leading to significant agricultural losses worldwide. These bacteria rapidly spread through the water-transporting xylem where they grow prolifically and produce abundant biofilm that clogs xylem vessels. To understand RSSC biofilm behavior in planta, we examined their complex fluid mechanics. Rheological analyses revealed that unlike all previously analyzed microbial biofilms, RSSC biofilms are shear-thinning, viscoelastic fluids at physiologically relevant shear forces. To determine which factors confer these unique mechanics, we analyzed biofilms of bacterial mutants with altered biofilm components. Genetic analysis demonstrated that development of the viscous-dominant biofilms required production of EPS-I, an amphiphilic exopolysaccharide that is a major virulence factor for all RSSC pathogens. We show that EPS-I confers “biofilm mobility”, which allows wild-type RSSC colonies to passively expand when deformed. Despite its high metabolic cost, bioassays demonstrated that EPS-I production conferred a net fitness benefit where biofilm mobility allowed the pathogen to spread and access more nutrients in complex environments like xylem vessels. The RSSC are a monophyletic lineage of aggressive plant wilt pathogens, and our evolutionary hypothesis testing suggests the origin of the eps biosynthetic gene cluster coincides with the emergence of wilt pathogenesis in the RSSC ancestor. Furthermore, comparative physiological assays demonstrated that biofilm mobility is unique to the RSSC within the genus Ralstonia . In summary, EPS-I production is a key evolutionary innovation that enables RSSC dispersal and virulence by conferring unique biofilm mechanics.